Arsenic, manganese, and iron concentration in groundwater of northwestern part of Bangladesh using self-organizing maps: Implication for health risk assessment - Obaida Urme; AHM Selim Reza; Md Ibrahim Adham; Golam Sabbir Sattar (Heliyon)
Quantification of the non-linear relationship between arsenic (As) and physico-chemical parameters in groundwater through a Self-Organizing Map (SOM) was performed for the first time in Chapai-Nawabganj, Bangladesh. Due to the continuous assessment of groundwater quality, the spatial distribution of As with associated elements was observed for the aerial extent of contaminated groundwater. The results exhibited that 57 % and 31 % of groundwater samples (n = 35) exceeded the allowable limit of As according to the WHO recommended drinking water standard (10 μg/L) and Bangladesh Drinking Water Standard (BDWS) (50 μg/L), respectively. The spatial distribution map of As demonstrated that a higher concentration of As in groundwater was found in the central portion of the study area and less amount was observed in the eastern part. Whereas 83 % of the samples for iron (Fe) concentration in groundwater surpassed the WHO guideline limit (0.3 mg/L) and were distributed all over the area except in the central part. Moreover, manganese (Mn) concentration varied from place to place within the allowable limit of WHO. The SOM analysis elucidated the non-linear relationship of As with other elements in two-dimensional planes of having 49 nodes (7 × 7), which incorporated with Spearman's correlation coefficient quantified the positive correlation among As, Mn and Ca, and negative correlation among As, Fe, EC and pH. In accordance with human health risk was also explained in terms of non-carcinogenic and carcinogenic risk. Health risk assessment demonstrated that higher health hazard (HQ) values in 57 % of the samples exceeded the threshold value for adults through the oral route, which implied the potential non-carcinogenic health risk, while 63 % of the samples for cancer risk (CR) was higher than the allowable limit indicating the considerable cancer risk zone for the residents of the area. This analysis provides information to the planners for formulating effective groundwater resources management and minimizing health sustainably.